Giganteone A and malabaricone C as potential pharmacotherapy for diabetes mellitus. Issue 6 (19th March 2022) - Sivasothy, Yasodha; Leong, Kok Hoong; Loo, Kong Yong; Adbul Wahab, Siti Mariam; Othman, Muhamad Aqmal; Awang, Khalijah
Abstract: The use of antidiabetic agents which control glycemic levels in the blood and simultaneously inhibit oxidative stress is an important strategy in the prevention of Diabetes Mellitus and its complications. In our previous study, malabaricone C (3 ) and its dimer, giganteone A (5 ) exhibited significant DPPH free radical scavenging activities which were lower than the activity of the positive control, ascorbic acid. These compounds were evaluated for their α-glucosidase inhibitory activities at different concentrations (0.02–2.5 mM) in the present study. Compounds 3 (IC50 59.61 µM) and 5 (IC50 39.52 µM) were identified as active alpha-glucosidase inhibitors, each respectively being 24 and 37 folds more potent than the standard inhibitor, acarbose. Based on the molecular docking studies, compounds 3 and 5 docked into the active site of the α-glucosidase enzyme, forming mainly hydrogen bonds in the active site. GRAPHICAL ABSTRACT: